Desafios ao Ensino da Tradução - Rodrigues, Cristina Carneiro [UNESP] (My University, 2012)
This paper aims to examine some challenges to translation training,particularly in the context of the discipline of translation theory, starting withthe belief in its impossibility. Other topics focused are the Italian adage traduttori,traditori, the opposition between theory and practice, the notion that thetranslator should not interfere in his/her work and the sacralization of the original text.

O objetivo deste artigo é examinar desafios ao ensino da tradução, especialmente no contexto da disciplina teoria da tradução, iniciando pela cren- ça em sua impossibilidade. Outros tópicos enfocados são o adágio italiano traduttori, traditori, a oposição entre teoria e prática, a noção de que o tradutor não deve interferir em seu trabalho e a sacralização do texto original.
Challenges to translators' training
Keywords: Estudos da Tradução; Impossibilidade; Infidelidade; Ensino da tradução